Clean Transfer of Large Graphene Single Crystals for High‐Intactness Suspended Membranes and Liquid Cells. Issue 26 (2nd May 2017) - Zhang, Jincan; Lin, Li; Sun, Luzhao; Huang, Yucheng; Koh, Ai Leen; Dang, Wenhui; Yin, Jianbo; Wang, Mingzhan; Tan, Congwei; Li, Tianran; Tan, Zhenjun; Liu, Zhongfan; et al.
Abstract : The atomically thin 2D nature of suspended graphene membranes holds promising in numerous technological applications. In particular, the outstanding transparency to electron beam endows graphene membranes great potential as a candidate for specimen support of transmission electron microscopy (TEM). However, major hurdles remain to be addressed to acquire an ultraclean, high‐intactness, and defect‐free suspended graphene membrane. Here, a polymer‐free clean transfer of sub‐centimeter‐sized graphene single crystals onto TEM grids to fabricate large‐area and high‐quality suspended graphene membranes has been achieved. Through the control of interfacial force during the transfer, the intactness of large‐area graphene membranes can be as high as 95%, prominently larger than reported values in previous works. Graphene liquid cells are readily prepared by π–π stacking two clean single‐crystal graphene TEM grids, in which atomic‐scale resolution imaging and temporal evolution of colloid Au nanoparticles are recorded. This facile and scalable production of clean and high‐quality suspended graphene membrane is promising toward their wide applications for electron and optical microscopy. Abstract : A polymer‐free transfer of sub‐centimeter graphene single crystals onto transmission electron microscopy (TEM) grids to fabricate high‐quality suspended graphene membranes is achieved. The intactness of 95% is prominently larger than previously reported values. High‐yield graphene liquid cells are fabricated via π–π stacking of two clean graphene TEM membranes, where atomic‐scale resolution imaging and temporal evolution of Au nanoparticles are recorded.